Transformaciones institucionales tendientes a captar financiamiento externo: características y dinámicas del endeudamiento de la economía argentina en los años noventa. (2015)
During the nineties Argentina’s foreign debt grew at an accelerated and incompatible rate with the viability of the in force convertibility regime. Foreign exchange earnings, their financial appraisal and subsequent remittance abroad became, over the years, the main mechanism of expansion of big business settled in the country. This article examines how the institutional reforms pushed on at the beginning of the decade enabled / fostered the implementation of this financial circuit, synthetically accounting for its nature and functions. This study was performed taking as empirical reference the laws through which these reforms were instrumentalized and the statistical data from secondary analysis sources.